UBE2B is implicated in myofibrillar protein loss in catabolic C2C12 myotubes. Issue 3 (19th November 2015) - Polge, Cécile; Leulmi, Roza; Jarzaguet, Marianne; Claustre, Agnes; Combaret, Lydie; Béchet, Daniel; Heng, Anne‐Elisabeth; Attaix, Didier; Taillandier, Daniel
Abstract: Background: Skeletal muscle protein loss is an adaptive response to various patho‐physiological situations, and the ubiquitin proteasome system (UPS) is responsible for the degradation of the bulk of muscle proteins. The role of E2 ubiquitin‐conjugating enzymes is still poorly understood in skeletal muscle. Methods: We screened for E2s expression levels in C2C12 myotubes submitted to the catabolic glucocorticoid dexamethasone (Dex). Results: One micromolar Dex induced an accumulation of proteasome substrates (polyUb conjugates) and an overexpression of the muscle‐specific E3 ligase MuRF1 and of six E2 enzymes, UBE2A, UBE2B, UBE2D1, UBE2D2, UBE2G1, and UBE2J1. However, only MuRF1 and UBE2B were sensitive to mild catabolic conditions (0.16 μM Dex). UBE2B knockdown induced a sharp decrease of total (−18%) and K48 (−28%) Ub conjugates, that is, proteasome substrates, indicating an important role of UBE2B in the overall protein breakdown in catabolic myotubes. Conclusions: Interestingly, these results indicate an important role of UBE2B on muscle protein homeostasis during catabolic conditions.